Transient deformation and heat generation of solid polyurethane under impact compression. (August 2017) - Pan, Zhongxiang; Xiong, Jie; Liang, Shixue; Zou, Meiling
Abstract: This investigation examines the transient deformation and heat generation of a solid polyurethane subjected to dynamic compression. A special method is presented to prepare the solid polyurethane from raw materials which are commonly used to make polyurethane foams. Testing methods including infrared spectrum, differential scanning calorimetry, quasi-static and dynamic compression were applied to study the basic physical properties of the solid polyurethane. High-speed optical and infrared imaging systems are used to obtain visual and thermo-graphic images during impact tests. Under quasi-static compression, the solid polyurethane presents a good performance in toughness. This is confirmed by its Poisson's ratio. Under impact compression, the adiabatic heat generation are identified statistically. Temperature distribution confirms the fact of transient heat generation in specimens. Adiabatic self-heating mechanism provides a consideration to understand the negative strain-rate effect and post-yield softening effect found in the solid polyurethane. Mechanical properties including quasi-static and dynamic responses are related with the composition of molecular and structure of polymer.